Analysis of the Impact of Audit Fee Reduction on Audit Quality and Stakeholder Trust - Rakhmadani, Nur Putra; Suzana, Suzi (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study analyzes the impact of audit fee reductions on audit quality and stakeholder trust, exploring the broader implications of constrained resources and their effects on corporate governance, financial reporting reliability, and stakeholder perceptions. Research Design and Methodology: Employing a qualitative approach through a systematic literature review (SLR), this study synthesizes findings from recent academic research across diverse contexts. Theoretical frameworks, particularly agency theory, are integrated to comprehensively understand the relationship between audit fees, audit quality, and stakeholder trust. Findings and Discussion: The findings reveal that reduced audit fees significantly impact the allocation of resources such as time, professional expertise, and technology, leading to diminished audit quality. This compromises the auditors' ability to detect material misstatements and affects their independence and professional skepticism. Lower audit quality, in turn, erodes stakeholder trust in financial statements, creating long-term reputational risks and market instability. Contextual factors, including regulatory frameworks and cultural dimensions, are identified as moderators that influence these dynamics. The study highlights the need for adequate audit fees to maintain transparency, accountability, and trust in financial reporting. Implications: This research contributes to the academic discourse by extending agency theory to include the financial and ethical challenges auditors face under cost constraints. Practically, it provides actionable insights for regulators, audit firms, and stakeholders, emphasizing the importance of balancing cost efficiency with audit quality. Recommendations include setting minimum audit fee standards, adopting advanced technologies, and enhancing auditor training to sustain trust and accountability in financial reporting systems.